2011
DOI: 10.1089/cyber.2011.0035
|View full text |Cite
|
Sign up to set email alerts
|

Facebook Tells Me So: Applying the Theory of Planned Behavior to Understand Partner-Monitoring Behavior on Facebook

Abstract: The social networking site (SNS) Facebook is becoming increasingly recognized as a medium through which individuals can investigate and monitor others' activities. However, little is known about whether Facebook monitoring behavior occurs within romantic relationships and, accordingly, the psychological predictors of this behavior. The present study employed an extended theory of planned behavior (TPB) framework including self-esteem, partner trust, and demographic characteristics, to predict frequent Facebook… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
53
1
9

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(67 citation statements)
references
References 20 publications
4
53
1
9
Order By: Relevance
“…According to Darvell, Walsh, and White (2011), Facebook provides a significant opportunity for people to inspect and investigate other users' activities, enabling access to their photos, personal information, opinions and discussions. Thus, this platform can be used for surveillance, allowing users to track the actions of others and to find information about people outside of their networks (Lampe, Ellison, & Steinfield, 2006).…”
Section: Facebook-obtained Gratification Factorsmentioning
confidence: 99%
“…According to Darvell, Walsh, and White (2011), Facebook provides a significant opportunity for people to inspect and investigate other users' activities, enabling access to their photos, personal information, opinions and discussions. Thus, this platform can be used for surveillance, allowing users to track the actions of others and to find information about people outside of their networks (Lampe, Ellison, & Steinfield, 2006).…”
Section: Facebook-obtained Gratification Factorsmentioning
confidence: 99%
“…However, the majority of the literature has concentrated on the profile owners themselves (Back et al, 2010;Carpenter, 2012) and their Facebook connection with families, school friends, and current or past significant others (Darvell, Walsh, & White, 2011;Jacobsen & Forste, 2011), who tend to be more involved in their private sphere. Few studies have focused on users' Facebook relationships with people from a more public sphere, the workplace, until the Yale Daily News reported that numerous employers have utilized Facebook to seek information about potential employees (Balakrishna, 2006).…”
Section: Two-way Interaction Between Gender Role and Benevolent Sexismentioning
confidence: 99%
“…When people interact on FB, there is a likelihood of people employing certain patterns of the language of their choice as Darvell, Walsh and White (2011) state that, people interact in various ways while on the internet. However, the three scholars do not go further to describe the patterns of this interaction event.…”
Section: Introductionmentioning
confidence: 99%
“…However, the three scholars do not go further to describe the patterns of this interaction event. In the present study, the interactions being referred to by Darvell, Walsh and White (2011) were analyzed in the SSIFB to examine the linguistic features employed by FB interlocutors.…”
Section: Introductionmentioning
confidence: 99%